Optimization of the yield of bacteriocin-like substance (BLIS) produced by Pediococcus pentosaceus and its application as food bioconservative - Azevedo, Pamela Oliveira de Souza de (2018)
Bacteriocins are peptides produced by various species of bacteria, especially lactic acid bacteria (LABs), which exhibit a large spectrum of action against spoilage bacteria and foodborne pathogens. However, when this bacteriocin has not been completely characterized regarding its amino acid and the nucleotide sequences of the corresponding gene, the qualified term bacteriocin-like inhibitory substance (BLIS) is recommended. In order to increase the antimicrobial activity of bacteriocins, the ability of probiotics LABs, such as Pediococcus pentosaceus, to ferment different carbon and nitrogen sources has been studied. For the development of an improved culture medium, carbon and nitrogen sources must be considered as nutrients responsible for cell growth and bacteriocin production. The best condition, after 48 h of cultivation, for growth (3.420 g/L) and for BLIS production by Pediococcus pentosaceus ATCC 43200 was in Man, Rogosa and Sharp (MRS) culture medium supplemented with 1.5% peptone, initial pH 6.0 and under the following culture conditions: anaerobiosis, 30oC and agitation of 200 rpm. Compared with control (MRS without supplement), the growth of Pediococcus was significantly lower (1.995 g/L) as well as it reduced significantly its generation time from 2.05 h (control) to 1.28 h (MRS supplemented), a reduction of approximately 62.5%. Moreover, addiction of peptone to MRS medium promoted reduction of 4 h to the Pediococcus exponential phase onset. Regarding BLIS antimicrobial activity, addition of nitrogen source to MRS medium was also quite significant. Through the agar diffusion method, BLIS showed inhibition halos between 12.50 and 19.50 mm against LABs strains (Lactobacillus sakei ATCC 15521, Lactobacillus plantarum CECT 221 and Carnobacterium piscicola CECT 4020). Against Listeria strains (Listeria innocua NCTC 111288 and Listeria seeligeri NCTC 11289), their antimicrobial activity was better detected in liquid medium assay, evaluating the minimal inhibitory concentration of 50%. BLIS was able to inhibit 60 and 100% of L. seeligeri and L. innocua, respectively, as well as, diluted 1x (v/v) in water was able to inhibit 100% growth of both Listeria. BLIS 17 showed also good results as food preservative when applied in ready-to-eat pork ham artificially contaminated with L. seeligeri in vacuum-package at 4oC during shelf life of 10 days. BLIS was able to maintain low Listeria multiplication, lower samples weight loss, low lipid peroxidation and good color parameters during samples storage. Results demonstrated the importance of optimizing the culture medium to increase microbial mass, to produce and to improve the activity of this antimicrobial molecule. Moreover, results also suggest the possible application of BLIS as a natural food preservative.